Association Between Fish Consumption and Muscle Mass and Function in Middle-Age and Older Adults - H, Maha; Alshammary, Modhi M. (Frontiers in Nutrition, 2021)
Background: Sarcopenia, the age-related loss of skeletal muscle mass and function, represents a crucial risk factor for disability and mortality [1]. Increasing intake of some nutrients, particularly protein and omega-3 fatty acids seems to be a promising strategy to augment muscle mass and function. Objective: The purpose of this study was to assess the beneficial effects of fish consumption on muscle mass and function among middle-age and older adults. Methods: Twenty-two adults aged 50–85 years participated in this study. Participats were asked to consume 150–170-g of fish for lunch twice a week for a 10-week period. During that period, participants were asked to maintain their normal diet and physical activity. Outcome measures included anthropometry, muscle mass, and muscle function. All these measures were assessed at baseline, week 5, and week 10. Repeated-measures analysis of variance was used to analyze statistical significance. Results: Consuming fish twice a week for 10 weeks significantly increased the skeletal muscle mass and appendicular lean mass divided by height squared (ALM/h2) (p < 0.01). Handgrip strength and gait speed < 0.8 m/s were also improved (p < 0.01) at week 10 compared with that at baseline. Discussion: Consuming fish seems to improve muscle mass and function and may slow sarcopenia progression in middle-age and older adults.